Terrorism and its Negative Effects on Sub-Saharan Africa: The Case of Al-Shabaab - Afriyie, Frederick Appiah (European Scientific Journal, ESJ, 2019)
In contemporary times, the most pressing issues threatening the tranquility and global stability, particularly in Africa, are the heinous activities of terrorist groups. The word â€œterrorismâ€ caught the worldâ€™s attention through the 9/11 incident, although it has been in existence for centuries. There have been numerous definitions for the act of terrorism, yet there is no universally approved definition which is accepted by all countries. This article, therefore, seeks to elucidate terrorism from different perspectives and also elaborate on its causes as well. Most importantly, this article focuses on Al-Shabaab as a violent extremist group with an emphasis on their background, their violent activities, the recruitment process as well as their source of funding. Additionally, their interconnection with the Al-Qaeda group will be dealt with as well as how terrorism has negatively affected a lot of people through the spread of violence, fear, and instability throughout the regions of Africa. The Al-Shabaab terrorist group in Somalia is considered amongst the deadliest militant groups across the continent of Africa, after the Boko Haram terrorist group in Nigeria. Some of the heinous activities carried out by this Al-Shabab terrorist group comprises of intimidation, bombing, suicide attacks, kidnapping, and gunfire of unarmed innocent citizens both within and outside Somalia. The inception of Al-Shabaab was as a result of the power vacuum that was created in 1991 after the warlords were unsuccessful in bringing into being any governance system during the fall of the last Somalia central government. Owing to this power vacuum fabricated, it has therefore empowered the Islamic court's leaders to assume informal authorities in some parts of south-central Somalia. Despite the fact that the Islamic court defeated these warlords, they were eventually defeated on the grounds of a national security threat by Ethiopian forces invading Somalia.